Inhibition of human gastric cancer growth by cytokine-induced killer cells plus chemotherapy with or without cadonilimab in a mouse xenograft tumor model - Yang, Wenwei; Liu, Jingwei; Hou, Tiantian; Lu, Xu; Yang, Lin (Frontiers in Immunology, 2025)
BackgroundCytokine-induced killer (CIK) cell therapy has shown potent antitumor cytotoxicity. To date, no study has evaluated the efficacy and safety of combining CIK cell therapy with chemotherapy, with or without the immune checkpoint inhibitor (ICI) cadonilimab, for treating gastric cancer (GC).MethodsIn vitro cytotoxicity, in vivo distribution, and acute toxicity of CIK cells were assessed. A nude mouse subcutaneous xenograft model of GC was established. To determine the antitumor effect of the CIK cells + chemotherapy regimen, 32 mice were randomized into the following four groups: control, CIK cells alone, chemotherapy alone, and CIK cells + chemotherapy. To evaluate the antitumor effect of CIK cells + chemotherapy supplemented with the cadonilimab regimen, mice subcutaneously inoculated with MGC803 cells were randomly assigned to the following eight experimental groups: vehicle, CIK cells, cadonilimab, chemotherapy, cadonilimab + chemotherapy, CIK cells + cadonilimab, CIK cells + chemotherapy, and CIK cells + cadonilimab + chemotherapy.ResultsIn vitro cytotoxicity assays indicated that CIK cells possessed good biocompatibility and sufficient therapeutic efficacy. An in vivo biodistribution assay revealed that CIK cells were mainly distributed in the spleen, lung, and liver. Acute toxicity analysis suggested that CIK cells had low toxicity. According to the tumor volume, the CIK cells + chemotherapy and chemotherapy-alone groups showed significantly higher tumor growth inhibition rates (34.2% and 50.8%, respectively) with well-tolerable toxicity than the control group (p < 0.01). The CIK cells + chemotherapy group exhibited a stronger, but not statistically significant, antitumor effect than the chemotherapy-alone group. In the safety and efficacy evaluation of CIK cells + chemotherapy + cadonilimab, the results showed that the tumor inhibitory effects of the cadonilimab + chemotherapy, CIK cells + chemotherapy, and CIK cells + cadonilimab + chemotherapy groups were significantly higher with tolerable toxicity than those of the CIK cells and cadonilimab groups (p < 0.05). The antitumor effect of the CIK cells + cadonilimab + chemotherapy regimen was also superior to that of the CIK cells + cadonilimab regimen (p = 0.0364). However, the tumor lysis ability showed no significant difference between the chemotherapy-based combination treatment groups and the chemotherapy-alone group.ConclusionsThe combination of CIK cells and chemotherapy with or without ICIs can serve as a potential therapeutic option for treating GC, with promising efficacy and good tolerability.